2001
DOI: 10.1152/jn.2001.86.6.3061
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cannabinoid CB1 Receptor Activation Inhibits Spinal Nociceptive Transmission In Vivo

Abstract: Cannabinoid1 (CB1) receptors are located at CNS sites, including the spinal cord, involved in somatosensory processing. Analgesia is one of the tetrad of behaviors associated with cannabinoid agonists. Here, effects of a potent cannabinoid CB1 receptor agonist arachidonyl-2-chloroethylamide (ACEA) on evoked responses of dorsal horn neurons in anesthetized rats were investigated. Extracellular recordings of convergent dorsal horn neurons were made in halothane anesthetized Sprague-Dawley rats (n = 16). Effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 10 publications
3
51
0
Order By: Relevance
“…These data are consistent with the presence of CB 1 receptors in the spinal dorsal horn (Tsou et al, 1998a;Hohmann et al, 1999a;Farquhar-Smith et al, 2000). Intrathecally-administered cannabinoids also produce antinociception (Yaksh, 1981;Smith and Martin, 1992;Welch and Stevens, 1992;Welch et al, 1995;Martin et al, 1999) and suppress noxious stimulus-evoked neuronal activity in spinal nociceptive neurons (Hohmann et al, 1998(Hohmann et al, , 1999bDrew et al, 2000;Kelly and Chapman, 2001), suggesting a functional role for spinal cannabinoid receptors in modulating nociceptive processing. Intrathecal administration of either rimonabant or CB 1 antisense oligonucleotides also elicits hyperalgesia (Richardson et al, 1998), suggesting that endocannabinoids may act tonically to suppress nociceptive responding.…”
Section: Introductionsupporting
confidence: 57%
“…These data are consistent with the presence of CB 1 receptors in the spinal dorsal horn (Tsou et al, 1998a;Hohmann et al, 1999a;Farquhar-Smith et al, 2000). Intrathecally-administered cannabinoids also produce antinociception (Yaksh, 1981;Smith and Martin, 1992;Welch and Stevens, 1992;Welch et al, 1995;Martin et al, 1999) and suppress noxious stimulus-evoked neuronal activity in spinal nociceptive neurons (Hohmann et al, 1998(Hohmann et al, , 1999bDrew et al, 2000;Kelly and Chapman, 2001), suggesting a functional role for spinal cannabinoid receptors in modulating nociceptive processing. Intrathecal administration of either rimonabant or CB 1 antisense oligonucleotides also elicits hyperalgesia (Richardson et al, 1998), suggesting that endocannabinoids may act tonically to suppress nociceptive responding.…”
Section: Introductionsupporting
confidence: 57%
“…The CB1 receptor agonist ACEA inhibits C-fiber-evoked responses in spinal dorsal horn neurons in normal and inflammatory pain models (Kelly and Chapman, 2001;Khasabova et al, 2004). Spinal administration of the non-selective cannabinoid receptor agonist HU210 reduces the C-fiber mediated response of spinal dorsal horn neurons only in spinal nerveinjured rats (Kelly and Chapman, 2001).…”
Section: Effect Of Cannabinoid Receptor Agonists On Synaptic Transmismentioning
confidence: 99%
“…Spinal administration of the non-selective cannabinoid receptor agonist HU210 reduces the C-fiber mediated response of spinal dorsal horn neurons only in spinal nerveinjured rats (Kelly and Chapman, 2001). However, for reducing Aδ-fiber-evoked responses, HU210 is effective in both sham-operated and nerve-injured rats (Chapman, 2001).…”
Section: Effect Of Cannabinoid Receptor Agonists On Synaptic Transmismentioning
confidence: 99%
“…[82][83][84][85][86][87][88][89][90] Walker ' s laboratory fi rst demonstrated that cannabinoids suppress noxious stimulus -evoked neuronal activity in nociceptive neurons in the spinal cord and thalamus. 84 , 85 , 88 , 91 , 92 This suppression is observed in nociceptive neurons, generalizes to different modalities of noxious stimulation (mechanical, thermal, chemical), is mediated by cannabinoid receptors, and correlates with the antinociceptive effects of cannabinoids.…”
Section: Cannabinoid-induced Suppression Of Nociceptive Transmissionmentioning
confidence: 99%